Heavy metal pollution characteristics and health evaluation of farmland soil in a gold mine slag area of Luoyang in China - Wang, Hui; Zhang, Hao; Xu, Renkou (International Journal of Agricultural and Biological Engineering, 2021)
The characteristics of eight heavy metals (lead, zinc, copper, nickel, chromium, cadmium, mercury and arsenic) in the surface soil of the historical slag area of the Au ore dressing plant in the South-West of Luoyang City were investigated and evaluated in terms of a pollution index, potential ecological hazards and health risks. The results showed that the average amounts of the heavy metals Pb, Zn and As in the soils of plots S3, S5, S7, S12 and S18 exceeded the soil pollution risk screening values. The Mero comprehensive pollution index in plots S7, S12 and S18 was greater than 3, indicating severe pollution. The severe pollution plot integrated the potential ecological risk index (RI) of each sampling point, which was in the order of RIS12 > RIS18 > RIS7 > RIS5 > RIS3. Among the heavy metals, Cd poses the greatest threat to ecological and human health. The effects of heavy metals in soil on the single non-carcinogenic health risk index (HQ) and the non-carcinogenic total risk index through three exposure pathways were in the order of HQHg < HQCu < HQNi < HQZn < HQCd < HQCr < HQPb < HQAs < 1, which meant that the adult and child total carcinogenic risk (TCR) and individual carcinogenic health risk indices were above the maximum acceptable human health level recommended by the USEPA (10-6). TCRAs and TCRCd accounted for 75.65% and 23.94% of the adult TCR, respectively. TCRAs and TCRCd accounted for 75.93% and 23.97% of the child TCR, respectively. Overall, the TCR of children was greater than that of adults. In summary, the soil in the historical slag area of the Au ore dressing plant constitutes a serious threat to the surrounding ecological environment and to residents. Keywords: historical slag area, heavy metals, pollution assessment, health assessment, farmland soil, ecological hazard DOI: 10.25165/j.ijabe.20211405.6536 Citation: Wang H, Zhang H, Xu R K. Heavy metal pollution characteristics and health evaluation of farmland soil in a gold mine slag area of Luoyang in China. Int J Agric & Biol Eng, 2021; 14(5): 213–221.